Cognitive Application Behavioral Therapy in Overcoming Dysthymia in Adolescents with Borderline Disorder Intellectual Functioning - Damayanti, Andini; Hartini, Nurul (Coution: Journal Counseling and Education, 2025)
Dysthymia, or Persistent Depressive Disorder, is a milder form of depression that lasts for years. This condition can cause problems in daily life and a decreased quality of life. Cognitive Behavioral Therapy (CBT) is an evidence-based approach proven effective in treating various mood disorders, including dysthymia. This study discusses the case of a 17-year-old female adolescent diagnosed with dysthymia and with an IQ of 70, thus categorized as borderline intellectual functioning. Symptoms that appeared were suicidal thoughts, hopelessness, low self-confidence, and fatigue. The client's condition was worsened by limited problem-solving abilities and inflexible thinking patterns. The assessments used were the Beck Depression Inventory (BDI), Millon Adolescent Clinical Inventory (MACI), SSCT (Sack's Sentence Completion Test), CFIT (Culture Fair Intelligence Test), and Graphic Tests (BAUM, DAP, HTP) which were used to determine the client's cognitive and emotional functioning. The intervention was structured, focusing on emotional regulation, cognitive restructuring, and improving coping skills. The intervention was repeated and simplified according to the client's understanding and interests. Results showed improvements in emotional regulation and social skills, improved self-perception, and reduced suicidal thoughts. These results indicate that CBT is effective and can be adapted for borderline intellectual functioning clients with dysthymia using simpler methods.